2023
DOI: 10.1093/trstmh/trad036
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of novel point-of-care diagnostics for febrile illnesses at health centres in Southeast Asia: a mixed-methods study

Fidelis Jacklyn Adella,
Moul Vanna,
Bipin Adhikari
et al.

Abstract: Background The decline of malaria in Southeast Asia means other causes of fever are increasingly relevant, but often undiagnosed. The objective of this study was to assess the feasibility of point-of-care tests to diagnose acute febrile illnesses in primary care settings. Methods A mixed-methods study was conducted at nine rural health centres in western Cambodia. Workshops introduced health workers to the STANDARD(TM) Q Deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…An operational study showed the potential of VMWs in executing additional roles, particularly in acquiring new knowledge and techniques about disease diagnosis and primary management. Although VMWs were able to use rapid diagnostic kits, the practical difficulty in using the dengue test was identified early on and may have important implications [ 24 ]. While any new techniques would inevitably require adequate and repeated training and supervision, some of the roles and responsibilities are difficult to implement and thus require careful consideration for the future [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An operational study showed the potential of VMWs in executing additional roles, particularly in acquiring new knowledge and techniques about disease diagnosis and primary management. Although VMWs were able to use rapid diagnostic kits, the practical difficulty in using the dengue test was identified early on and may have important implications [ 24 ]. While any new techniques would inevitably require adequate and repeated training and supervision, some of the roles and responsibilities are difficult to implement and thus require careful consideration for the future [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiplexed biosensors were designed to test malaria (four Plasmodium species, using pLDH and HRP2), dengue virus, zika virus, chikungunya virus, leptospirosis, Rickettsia typhi , Burkholderia pseudomallei , and Orientia tsutsugamushi . [ 24 ]. The full report on the deployment of novel RDTs is under preparation (Visser et al 2023).…”
Section: New Diagnostics For Village Malaria Workersmentioning
confidence: 99%
See 2 more Smart Citations
“…We reflect on our engagement with CHWs related to malaria on how their roles and contributions could be optimised for malaria control and elimination. 15–18 Table 1 provides an overview comparing the CHW network in Cambodia with Tanzania ( table 1 ).…”
Section: Comparison Between Cambodia and Tanzaniamentioning
confidence: 99%